Konstruksi Patriarki Dalam Pembagian Peran Gender dan Beban Ganda Perempuan Dalam Komunikasi Sosial - Dafina Nur Khodijah; Nina Yuliana (Prisani Cendekia Institute, 2026)
Gender inequality remains a persistent issue in social life, particularly reflected in the unequal division of gender roles between men and women. Within patriarchal cultures, women are commonly associated with domestic responsibilities, while men are positioned as dominant actors in the public sphere. This unequal division of roles creates imbalanced power relations and contributes to the emergence of women’s double burden. This study aims to analyze the construction of patriarchy in the division of gender roles and its implications for women’s double burden within the context of social communication. The research employs a qualitative approach through a literature study, drawing on a social philosophy perspective to understand patriarchy as a structure of power relations, while communication studies are used to explain how patriarchal values are constructed and reproduced through everyday social communication practices. The findings indicate that patriarchy operates not only as a social system but also as a meaning-making process reproduced through language, social interactions, and media representations. These communication practices play a significant role in normalizing unequal gender roles and sustaining women’s double burden. Therefore, communication studies are essential for fostering critical reflection on social communication practices that continue to reproduce gender inequality.